Genome-wide association analyses of invasive pneumococcal isolates identify a missense bacterial mutation associated with meningitis - Yuan Li (Nature Portfolio, 2019)
Meningitis is a severe form of invasive pneumococcal disease (IPD). To study the contribution of bacterial genomic variation, here Li et al. perform whole genome sequencing of pneumococcal isolates from IPD patients and identify an association for higher risk of meningitis with a pbp1bA641C variant